Finite element analysis of electroactive polymer and magnetoactive elastomer based actuation for origami folding. (13th September 2017) - Zhang, Wei; Ahmed, Saad; Masters, Sarah; Ounaies, Zoubeida; Frecker, Mary
Abstract: The incorporation of smart materials such as electroactive polymers and magnetoactive elastomers in origami structures can result in active folding using external electric and magnetic stimuli, showing promise in many origami-inspired engineering applications. In this study, 3D finite element analysis (FEA) models are developed using COMSOL Multiphysics software for three configurations that incorporate a combination of active and passive material layers, namely: (1) a single-notch unimorph folding configuration actuated using only external electric field, (2) a double-notch unimorph folding configuration actuated using only external electric field, and (3) a bifold configuration which is actuated using multi-field (electric and magnetic) stimuli. The objectives of the study are to verify the effectiveness of the FEA models to simulate folding behavior and to investigate the influence of geometric parameters on folding quality. Equivalent mechanical pressure and surface stress are used as external loads in the FEA to simulate electric and magnetic fields, respectively. Compared quantitatively with experimental data, FEA captured the folding performance of electric actuation well for notched configurations and magnetic actuation for a bifold structure, but underestimated electric actuation for the bifold structure. By investigating the impact of geometric parameters and locations to place smart materials, FEA can be used in design, avoiding trial-and-error iterations of experiments.